Transformasi Norma Adat dalam Hantaran Pernikahan Gorontalo: Analisis Hukum Adat dan Hukum Keluarga Islam terhadap Pergeseran Nilai Simbolik - Hamid Pongoliu; Muhammad Gazali Rahman; Syukrin Nurkamiden; Ajub Ishak; Dikson Yasin (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
This study examines the transformation of customary norms in the practice of wedding gifts (hantaran) within the Gorontalo marriage tradition from the perspectives of customary law and Islamic family law. Unlike previous studies that primarily emphasize the symbolic meanings of wedding gifts as cultural heritage, this research positions hantaran as a normative institution of customary law that functions to transmit legal, moral, and social values concerning family life. Employing an empirical legal method with a socio-legal approach, the study integrates legal anthropology, customary law, and Islamic family law through interviews, observations, and documentary analysis. The findings reveal that the symbolic meanings of hantaran have undergone significant transformation due to modernization, urbanization, economic rationalization, and the influence of digital media. The shift reflects a movement from normative functions toward symbolic and representational functions without entirely eliminating the existence of customary law as living law. From the perspective of customary law, this transformation represents an adaptive process of legal culture, whereas Islamic family law recognizes such changes insofar as they remain consistent with the principles of al-'ādah al-muḥakkamah, 'urf ṣaḥīḥ, and maqāṣid al-syarī'ah. This study proposes a reconstructive model that emphasizes preserving the normative values of customary traditions rather than merely maintaining their ceremonial forms, thereby strengthening the integration of customary law and Islamic family law in responding to contemporary social change.